A phlorotannin constituent of Ecklonia cava alleviates postprandial hyperglycemia in diabetic mice - Hyun-Ah Lee; Ji-Hyeok Lee; Ji-Sook Han (Taylor & Francis Group, 2017)
Context: 2,7"-Phloroglucinol-6,6'-bieckol is a type of phlorotannin isolated from brown algae, Ecklonia cava Kjellman (Phaeophyceae; Laminareaceae). 2,7"-Phloroglucinol-6,6'-bieckol mediates antioxidant activities. However, there has been no research on improving postprandial hyperglycaemia using 2,7"-phloroglucinol-6,6'-bieckol. Objective: This study investigated the inhibitory effects of 2,7"-phloroglucinol-6,6'-bieckol on activities of α-glucosidase and α-amylase as well as its alleviating effect on postprandial hyperglycaemia in streptozotocin-induced diabetic mice. Materials and methods: α-Glucosidase and α-amylase inhibitory assays were carried out. The effect of 2,7"-phloroglucinol-6,6'-bieckol on hyperglycaemia after a meal was measured by postprandial blood glucose in streptozotocin-induced diabetic and normal mice. The mice were treated orally with soluble starch (2 g/kg BW) alone (control) or with 2,7"-phloroglucinol-6,6'-bieckol (10 mg/kg bw) or acarbose (10 mg/kg BW) dissolved in 0.2 mL water. Blood samples were taken from tail veins at 0, 30, 60, and 120 min and blood glucose was measured by a glucometer. Results: 2,7"-Phloroglucinol-6,6'-bieckol showed higher inhibitory activities than acarbose, a positive control against α-glucosidase and α-amylase. The IC50 values of 2,7"-phloroglucinol-6,6'-bieckol against α-glucosidase and α-amylase were 23.35 and 6.94 μM, respectively, which was found more effective than observed with acarbose (α-glucosidase IC50 of 130.04 μM; α-amylase IC50 of 165.12 μM). In normal mice, 2,7"-phloroglucinol-6,6'-bieckol significantly suppressed the postprandial hyperglycaemia caused by starch. The 2,7"-phloroglucinol-6,6'-bieckol administration group (2349.3 mmol·min/L) had a lower area under the curve (AUC) glucose response than the control group (2690.83 mmol·min/L) in diabetic mice. Discussion and conclusion: 2,7"-Phloroglucinol-6,6'-bieckol might be used as an inhibitor of α-glucosidase and α-amylase as well as to delay absorption of dietary carbohydrates.